Use of interactive worksheets to teach speaking - Haris Dibdya; Hendra Sudarso (English Teaching Journal : A Journal of English Literature, Language and Education, 2023)
The goal of the study is to illustrate how Interactive Worksheets for teaching speaking is used.   Interactive Worksheet is an online interactive worksheet that was created by a lecture to encourage students to speak more. Students can record their speaking and they can get their speaking score instantly. The research uses descriptive qualitative research as its method and design. Online Interactive Worksheet, students and the result of the worksheet are the data's sources. Data collection methods include observing, interviewing, and documenting. Triangulation methodology is used by the researcher to determine the veracity of the data. Data analysis techniques include data condensing, data displaying, conclusion, and verification. The study's findings indicate that: First, help students pronounce the word correctly. Second, encourage someone to speak. Third, work on improving the students' speaking skills.  Make speaking fun for the students, and that's all. The disadvantage, is challenging for pupils to understand the meaning of a term in the text and pronounce correctly. In addition, students can look up a challenging word in a dictionary. The researcher offers recommendations in this study for the teacher, students, school, and other researchers.